Welcome to the Journal of Amateur Sport! - Bass, Jordan R. (Journal of Amateur Sport, 2015)
Welcome to the first issue of the Journal of Amateur Sport (JAS)! First, I must thank everyone who played an integral role in the development of JAS. Drs. Mark Vermillion, Brian Gordon, Kyle Bunds, and Marion Hambrick were invaluable in their guidance as original members of the editorial and development team. The first editorial board has also played a large part in the excellent quality of the first issue that follows. We hope you enjoy this issue and look forward to receiving your submissions in the future!